A composite shielding light-weight wire harness for a new energy vehicle gas circulating fan and a manufacturing method thereof

CN123017609APending Publication Date: 2026-10-30HANGZHOU WAHO ELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611287944.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

硅橡胶具有较宽的使用温度范围和良好的柔韧性,但硅橡胶表面硬度和耐磨性相对较低,在线束装配、振动摩擦和长期弯折过程中容易受到机械损伤

Benefits of technology

本申请中在电力传输导线和信号传输导线外分别设置由硅橡胶内绝缘层和交联聚乙烯外绝缘层构成的复合绝缘层,使硅橡胶内绝缘层的耐高低温性、柔韧性与交联聚乙烯外绝缘层的绝缘强度、耐磨性和机械防护性能相结合,再利用复合绝缘层、复合屏蔽层、护套层以及一体化注塑密封连接器的配合,提高了新能源汽车气体循环风机线束的耐高低温性能、抗弯曲疲劳性能、抗电磁干扰性、防水密封性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of new energy automobile electrical connection and wire harness manufacturing, and specifically discloses a composite shielding lightweight wire harness for a new energy automobile gas circulating fan and a manufacturing method thereof. The composite shielding lightweight wire harness for the new energy automobile gas circulating fan comprises bundled wires, a composite shielding layer wrapped outside the bundled wires, a sheath layer wrapped outside the composite shielding layer, and an integrated injection-molded sealing connector arranged at the end of the wire harness and branch points; the bundled wires comprise at least one power transmission wire wrapped with a composite insulation layer and at least one signal transmission wire wrapped with a composite insulation layer; the composite insulation layer comprises a silicone rubber inner insulation layer wrapped outside the wire and a crosslinked polyethylene outer insulation layer wrapped outside the silicone rubber inner insulation layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of electrical connection and wiring harness manufacturing for new energy vehicles, and in particular to a composite shielded lightweight wiring harness for gas circulation fans in new energy vehicles and its manufacturing method. Background Technology

[0002] As new energy vehicles develop towards higher voltage, higher power density, and greater integration, the number of gas circulation fans used in battery thermal management systems, fuel cell air supply and circulation systems, and cabin ventilation and purification systems is gradually increasing. Gas circulation fans typically need to operate for extended periods in environments with alternating high and low temperatures, continuous vibration, humidity, salt spray, and complex electromagnetic interference. Their wiring harnesses not only transmit the power to drive the fan but also transmit control signals such as speed, temperature, current, and fault feedback. Therefore, gas circulation fan wiring harnesses must simultaneously possess excellent high and low temperature resistance, electrical insulation properties, flexibility, vibration fatigue resistance, wear resistance, electromagnetic shielding, and waterproof sealing properties.

[0003] Existing wiring harnesses for gas circulation fans in new energy vehicles typically include power transmission conductors, signal transmission conductors, a shielding layer, a sheathing layer, and connectors. During the wiring harness manufacturing process, insulation layers are generally extruded onto each power transmission conductor and signal transmission conductor to form mutually insulated power transmission conductors and signal transmission conductors. These insulated conductors are then twisted together in a predetermined manner to form a cable core, and a shielding layer and a sheathing layer are sequentially installed around the cable core.

[0004] Currently, wire harness insulation layers commonly use materials such as polyvinyl chloride (PVC), ordinary polyethylene (PE), cross-linked polyolefins (CPE), or silicone rubber. PVC and PE offer good processing performance and low cost, but their high-temperature resistance and long-term thermal aging resistance are limited. When used for extended periods in the high-temperature compartments of new energy vehicles, they are prone to insulation hardening, cracking, and a decrease in elongation at break. CPE possesses high insulation strength, abrasion resistance, and heat resistance, but its flexibility at low temperatures and fatigue resistance under repeated bending conditions still have room for improvement. Silicone rubber has a wide operating temperature range and good flexibility, but its surface hardness and abrasion resistance are relatively low, making it susceptible to mechanical damage during wire harness assembly, vibration friction, and long-term bending.

[0005] Therefore, existing wiring harnesses for gas circulation fans in new energy vehicles still suffer from problems such as insufficient stability of the interface bonding of the insulation layer, easy delamination after high and low temperature cycling, low dynamic bending fatigue life, difficulty in achieving both inorganic filler reinforcement and flexibility, mismatch of cross-linking processes for different insulation materials, and difficulty in synergistically improving the shielding, sealing and lightweight performance of the wiring harness. Summary of the Invention

[0006] In order to improve the high and low temperature resistance, bending fatigue resistance, electromagnetic interference resistance, and waterproof sealing performance of the wiring harness for gas circulation fans in new energy vehicles, this application provides a composite shielded lightweight wiring harness for gas circulation fans in new energy vehicles and its manufacturing method.

[0007] In the first aspect, this application provides a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle, which adopts the following technical solution: A composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle includes bundled conductors, a composite shielding layer covering the outside of the bundled conductors, a sheath layer covering the outside of the composite shielding layer, and an integrated injection-molded sealed connector disposed at the ends and branches of the wiring harness. The bundled conductors include at least one power transmission conductor covered with a composite insulation layer and at least one signal transmission conductor covered with a composite insulation layer. The composite insulation layer includes a silicone rubber inner insulation layer covering the outside of the conductors and a cross-linked polyethylene outer insulation layer covering the outside of the silicone rubber inner insulation layer. The raw material of the silicone rubber inner insulation layer comprises the following components in parts by weight: silicone rubber matrix 1... The raw materials for the cross-linked polyethylene outer insulation layer include the following components by weight: 100 parts of polyolefin resin matrix, 4-8 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 2-6 parts of bifunctional interface bridging particles, and 4-6 parts of silanol condensation catalyst masterbatch; the bifunctional interface bridging particles include an inorganic core, a silica shell coating the surface of the inorganic core, and vinyl silane and amino silane grafted onto the surface of the silica shell.

[0008] By adopting the above technical solutions, the fumed silica in the inner insulation layer of silicone rubber can reinforce the silicone rubber matrix, improving the tensile strength, tear resistance, and dimensional stability of the inner insulation layer; hydroxyl silicone oil can reduce the interaction between hydroxyl groups on the surface of fumed silica, inhibit the structuring and agglomeration of silica, and improve the dispersion uniformity and mixing performance of each component in the silicone rubber matrix; vinyl silicone oil can both adjust the flexibility of the inner insulation layer and participate in the crosslinking reaction initiated by peroxide, thereby adjusting the uniformity and crosslinking density of the silicone rubber crosslinking network. The ethylene-methyl acrylate-glycidyl methacrylate copolymer in the cross-linked polyethylene outer insulation layer contains epoxy groups, which can undergo ring-opening reactions with the amino groups on the surface of the bifunctional interfacial bridging particles. The vinyl groups on the surface of the bifunctional interfacial bridging particles can participate in the cross-linking of the silicone rubber matrix under the action of peroxide cross-linking agents. Therefore, the same bifunctional interfacial bridging particle can form chemical connections with the silicone rubber inner insulation layer and the cross-linked polyethylene outer insulation layer respectively, forming a cross-interface reactive bridging structure between the two layers. The reactive bridging structure can reduce the interfacial porosity and weak physical bonding areas between the silicone rubber inner insulation layer and the cross-linked polyethylene outer insulation layer, improve the interfacial bonding strength of the two materials, and help suppress interfacial slippage, crack propagation, and interlayer delamination of the composite insulation layer during high and low temperature cycling, vibration, and dynamic bending. The bifunctional interface bridging particles employ an inorganic core and a silica shell structure. The silica shell increases the number of surface active sites available for silane grafting and improves the compatibility between the inorganic core and organic insulating materials, reducing interface defects caused by direct exposure of inorganic particles. Therefore, while maintaining the insulation performance and flexibility of the composite insulation layer, it improves interface stability, mechanical strength, and thermal cycling durability. The composite shielding layer is set on the outside of the bundled wires, which can reduce the impact of electromagnetic interference generated during power transmission on the signal transmission wires and reduce the interference of external electromagnetic fields on the fan control signals; the sheath layer can provide mechanical, wear-resistant and environmental protection for the composite shielding layer and the internal bundled wires; the integrated injection-molded sealed connectors set at the ends and branches of the wire harness can reduce the entry of water vapor, salt spray and pollutants from the ends or branches of the wire harness, and improve the sealing performance and vibration resistance reliability of the wire harness. Therefore, by utilizing the combination of composite insulation layer, composite shielding layer, sheath layer and integrated injection-molded sealed connector, the high and low temperature resistance, bending fatigue resistance, electromagnetic interference resistance and waterproof sealing performance of the gas circulation fan wiring harness for new energy vehicles are improved.

[0009] In one specific implementation, the silicone rubber matrix comprises methyl vinyl silicone rubber and methyl vinyl phenyl silicone rubber in a mass ratio of (75-90):(10-25).

[0010] By adopting the above technical solutions, methyl vinyl silicone rubber possesses excellent heat resistance, electrical insulation, and processing performance, and can form the main cross-linked network of the inner insulating layer of silicone rubber. The methyl vinyl phenyl silicone rubber molecular chain contains phenyl side groups, which can change the regularity of the polysiloxane molecular chain, reduce the crystallization tendency of silicone rubber in low-temperature environments, and enable the inner insulating layer to maintain good elasticity and bending performance under low-temperature conditions. The combination of the two can achieve a balance between high-temperature resistance, low-temperature flexibility, mechanical strength, and processing fluidity. In addition, both silicone rubbers contain vinyl groups that can participate in peroxide cross-linking, which can enter the cross-linked network together with the vinyl groups on the surface of the bifunctional interface bridging particles, thereby improving low-temperature performance while maintaining the chemical connection between the bifunctional interface bridging particles and the silicone rubber matrix.

[0011] In one specific implementation, the raw material of the silicone rubber inner insulating layer further includes 1 to 4 parts by weight of phenyl silicone oil.

[0012] By adopting the above technical solution, both phenyl silicone oil and methyl vinyl phenyl silicone rubber contain phenyl structures and have good compatibility. Phenyl silicone oil can enter between the molecular chains of silicone rubber, reducing the restriction on molecular chain movement under low temperature conditions, thereby further improving the low-temperature flexibility, flexural recovery and low-temperature brittleness resistance of the inner insulating layer of silicone rubber. In addition, phenyl silicone oil can also improve the processing fluidity of silicone rubber compound, promote the uniform dispersion of fumed silica and bifunctional interface bridging particles, and reduce local stress concentration points and dielectric defects caused by inorganic particle agglomeration.

[0013] In one specific implementation, the polyolefin resin matrix comprises silane-modified polyethylene, metallocene linear low-density polyethylene, and ethylene-octene copolymer, in a mass ratio of (65-78):(8-15):(10-18).

[0014] By adopting the above technical solution, the three polyolefin materials used together provide a heat-resistant cross-linking network, metallocene linear low-density polyethylene improves processing and thin-wall molding performance, and ethylene-octene copolymer provides flexibility, toughening and stress buffering effects, thus helping to balance the heat resistance, wear resistance, flexibility and interface durability of the outer insulation layer.

[0015] In one specific implementation, the method for preparing the bifunctional interface bridging particles includes the following steps: 100 parts by weight of nano-alumina were dispersed in 250-350 parts by weight of anhydrous ethanol, 20-30 parts by weight of deionized water and 2-3 parts by weight of ammonia were added, 30-40 parts by weight of tetraethyl orthosilicate were added dropwise, and the reaction was carried out at 40-60℃ for 2-4 hours. After filtration, washing and drying, core-shell particles coated with a silica shell were obtained. 100 parts by weight of core-shell particles were dispersed in a mixture of 100-180 parts by weight of ethanol and 5-12 parts by weight of deionized water. 2.0-4.0 parts by weight of vinyltriethoxysilane and 0.5-1.5 parts by weight of γ-aminopropyltriethoxysilane were added, and the pH of the system was adjusted to 4.5-5.5. The mixture was reacted at 55-70°C for 2-4 hours. After filtration, washing, and vacuum drying at 90-110°C, bifunctional interfacial bridging particles were obtained.

[0016] By adopting the above technical solution, a silica shell is first formed on the surface of nano-alumina using sol-gel reaction, resulting in core-shell particles with nano-alumina as the core and silica as the shell. Then, vinyltriethoxysilane and γ-aminopropyltriethoxysilane are grafted onto the core to obtain bifunctional interface bridging particles.

[0017] In one specific implementation, the raw material of the silicone rubber inner insulating layer further includes 0.5 to 1.5 parts by weight of nano-cerium oxide.

[0018] By adopting the above technical solution, the addition of nano-cerium oxide can improve the long-term heat aging resistance of the inner insulation layer of silicone rubber; and nano-cerium oxide, together with fumed silica and bifunctional interface bridging particles, can form a multi-scale inorganic reinforcement system in the silicone rubber matrix, thereby synergistically improving the mechanical reinforcement, interface stability and heat aging resistance of the inner insulation layer.

[0019] In one specific implementation scheme, the raw material of the cross-linked polyethylene outer insulation layer further includes the following components in parts by weight: 0.2 to 0.4 parts of hindered phenolic antioxidant, 0.1 to 0.3 parts of phosphite antioxidant, and 0.2 to 0.5 parts of copper ion inhibitor.

[0020] By adopting the above technical solutions, the combined use of hindered phenolic antioxidants, phosphite antioxidants, and copper ion inhibitors can inhibit the thermo-oxidative aging of the cross-linked polyethylene outer insulation layer from three aspects: free radical capture, hydrogen peroxide decomposition, and metal ion passivation. This is beneficial to improving the elongation at break, crack resistance, and electrical insulation stability of the outer insulation layer under long-term high-temperature conditions.

[0021] Secondly, this application provides a method for manufacturing a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle, which adopts the following technical solution: A method for manufacturing a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle includes the following steps: Mixing: The silicone rubber matrix, fumed silica, bifunctional interface bridging particles, hydroxyl silicone oil and vinyl silicone oil are mixed, and a peroxide crosslinking agent is added at a mixing temperature not higher than 60°C to obtain silicone rubber internal insulating compound. Melt blending: Polyolefin resin matrix, ethylene-methyl acrylate-glycidyl methacrylate copolymer, and bifunctional interfacial bridging particles are melt blended and granulated, and then mixed with silanol condensation catalyst masterbatch to obtain cross-linked polyethylene external insulation composition; Inner layer extrusion: The silicone rubber inner insulation compound is extruded and coated onto the surface of the power transmission wire and signal transmission wire, and the extruded silicone rubber inner insulation layer is pre-vulcanized. Extrusion of outer layer: Cross-linked polyethylene outer insulation composition is extruded on the outside of the pre-vulcanized silicone rubber inner insulation layer to obtain power transmission wires and signal transmission wires covered with composite insulation layer; Stranded composite: Power transmission wires and signal transmission wires covered with composite insulation layers are first wet-crosslinked and then stranded to form bundled wires. A composite shielding layer and a sheath layer are applied sequentially to the outside of the bundled wires, and the ends and branches of the wire harness are integrally injection-molded and sealed to obtain a composite shielded lightweight wire harness for gas circulation fans of new energy vehicles.

[0022] By adopting the above technical solution, the inner insulation material is first mixed, then the outer insulation material is melted and blended, and then extruded onto the conductors respectively. After being stranded into a bundle of conductors, a composite shielding layer and a sheath layer are applied in sequence, and the ends and branches of the wire harness are integrally injection molded and sealed to obtain a composite shielded lightweight wire harness for gas circulation fans of new energy vehicles.

[0023] In one specific implementation, in the stranding and composite step, the composite shielding layer includes an aluminum foil wrapping layer and a tin-plated copper wire braided mesh.

[0024] By adopting the above technical solutions, the aluminum foil wrapping layer has a high surface coverage, which can form a relatively continuous electric field shielding layer and has a good blocking effect on medium and high frequency electromagnetic interference; the tin-plated copper wire braided mesh has low resistance and good mechanical flexibility, which can provide a grounding current path and shield low frequency electromagnetic interference; when the two are used together, the shielding performance, mechanical protection performance and grounding reliability of different frequency bands are synergistically improved.

[0025] In one specific implementation, in the stranding and bonding step, the raw material of the sheath layer includes thermoplastic polyester elastomer with a thickness of 0.5-1.0 mm.

[0026] By adopting the above technical solution, the thickness of the sheath layer is limited to 0.5-1.0mm, which helps to reduce the amount of sheath material used and reduce the outer diameter and weight of the wire harness.

[0027] In summary, this application includes at least one of the following beneficial technical effects: In this application, a composite insulation layer consisting of an inner silicone rubber insulation layer and an outer cross-linked polyethylene insulation layer is respectively provided on the outside of the power transmission wire and the signal transmission wire. This combines the high and low temperature resistance and flexibility of the inner silicone rubber insulation layer with the insulation strength, wear resistance and mechanical protection performance of the outer cross-linked polyethylene insulation layer. Furthermore, by utilizing the composite insulation layer, composite shielding layer, sheath layer and integrated injection-molded sealing connector, the high and low temperature resistance, bending fatigue resistance, electromagnetic interference resistance and waterproof sealing performance of the new energy vehicle gas circulation fan wiring harness are improved. When the three polyolefin materials are used together in this application, silane-modified polyethylene provides a heat-resistant crosslinking network, metallocene linear low-density polyethylene improves processing and thin-wall molding performance, and ethylene-octene copolymer provides flexibility, toughening and stress buffering effects, thereby helping to balance the heat resistance, wear resistance, flexibility and interface durability of the outer insulation layer. The method in this application involves first mixing the inner insulation material, then melting and blending the outer insulation material, then extruding them onto the conductors, twisting them into a bundle of conductors, then sequentially applying a composite shielding layer and a sheath layer, and finally performing integrated injection molding sealing at the ends and branches of the wire harness to obtain a composite shielded lightweight wire harness for gas circulation fans in new energy vehicles. Detailed Implementation

[0028] The present application will be further described in detail below with reference to the embodiments.

[0029] All raw materials used in the examples are commercially available. The hindered phenolic antioxidant is Antioxidant 1010; the phosphite antioxidant is Antioxidant 168; the silanol condensation catalyst masterbatch is Borealis Visico™ LE4437; the copper ion inhibitor is BASF Irganox® MD 1024; the silane-modified polyethylene is Borealis Visico™ LE4423; the metallocene linear low-density polyethylene is a metallocene-catalyzed ethylene-1-hexene copolymer, model Exceed m 3518.CBWire & Cable; the ethylene-octene copolymer is Dow ENGAGE™ 8150; the hydroxyl silicone oil is α,ω-dihydroxypolydimethylsiloxane; the vinyl silicone oil is α,ω-divinyl polydimethylsiloxane; the phenyl silicone oil is methylphenyl polysiloxane; and the hot-melt polyamide for low-pressure injection molding is Henkel TECHNOMELT® PA 673 N. Preparation Example

[0030] Preparation Example 1 Preparation Example 1 provides a method for preparing bifunctional interface-bridged particles, comprising the following steps: Nano-alumina was dispersed in anhydrous ethanol, deionized water and 25% ammonia were added, and tetraethyl orthosilicate was added dropwise. The mixture was stirred at 550 r / min and 50℃ for 3 h. After filtration and washing, the mixture was dried at 80℃ for 8 h. The dried core-shell particles were then ground and passed through a 200-mesh sieve to obtain core-shell particles coated with a silica shell. The weight ratio of nano-alumina, anhydrous ethanol, deionized water, ammonia, and tetraethyl orthosilicate was 100:300:25:2.5:35. Core-shell particles were dispersed in a mixture of ethanol and deionized water. Vinyltriethoxysilane and γ-aminopropyltriethoxysilane were added. The pH of the system was adjusted to 5.0 using a 10% (w / w) aqueous acetic acid solution. The mixture was stirred at 500 rpm and reacted at 60°C for 3 h. After filtration, washing, and vacuum drying at 100°C for 10 h, the mixture was ground and passed through a 200-mesh sieve to obtain bifunctional interface bridging particles. The weight ratio of core-shell particles, ethanol, deionized water, vinyltriethoxysilane, and γ-aminopropyltriethoxysilane was 100:140:8.5:3:1.

[0031] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the core-shell particles were dispersed in a mixture of ethanol and deionized water, vinyltriethoxysilane was added, and the pH of the system was adjusted to 5.0 using a 10% (w / w) aqueous solution of acetic acid. The mixture was stirred at 500 r / min and reacted at 60°C for 3 h. After filtration, washing, and vacuum drying at 100°C for 10 h, the mixture was ground and passed through a 200-mesh sieve to obtain bifunctional interface bridging particles. The weight ratio of core-shell particles, ethanol, deionized water, and vinyltriethoxysilane was 100:140:8.5:4. The remaining steps were the same as in Preparation Example 1.

[0032] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the core-shell particles were dispersed in a mixture of ethanol and deionized water, γ-aminopropyltriethoxysilane was added, the pH of the system was adjusted to 5.0 using a 10% (w / w) aqueous solution of acetic acid, and the reaction was carried out at 500 r / min and 60°C for 3 h. After filtration, washing, and vacuum drying at 100°C for 10 h, the particles were ground and passed through a 200-mesh sieve to obtain bifunctional interface bridging particles. The weight ratio of core-shell particles, ethanol, deionized water, and γ-aminopropyltriethoxysilane was 100:140:8.5:4. The remaining steps were the same as in Preparation Example 1. Example

[0033] Example 1 Example 1 provides a method for manufacturing a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle, comprising the following steps: Mixing: 100 kg of silicone rubber matrix was added to an internal mixer and plasticized for 5 min at a rotor speed of 25 r / min and a cooling water temperature of 20 °C. The temperature was 45 °C. Then, 20 kg of fumed silica, 4 kg of bifunctional interface bridging particles from Preparation Example 1, 2 kg of hydroxyl silicone oil, and 1 kg of vinyl silicone oil were added and mixed for 13 min at a speed of 35 r / min. Then, 0.6 kg of peroxide crosslinking agent was added at 30 °C to obtain silicone rubber internal insulating compound. The silicone rubber matrix was methyl vinyl silicone rubber and methyl vinyl phenyl silicone rubber in a mass ratio of 85:15. The peroxide crosslinking agent was 2,5-dimethyl-2,5-di-tert-butylperoxyhexane. Melt blending: 100 kg of polyolefin resin matrix, 4 kg of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 0.2 kg of hindered phenolic antioxidant, 0.1 kg of phosphite antioxidant, and 0.2 kg of copper ion inhibitor were first mixed at 300 r / min for 3 min, and then mixed at 600 r / min for 5 min to obtain a premix. The premix and 2 kg of bifunctional interface bridging particles from Preparation Example 1 were added to a co-rotating twin-screw extruder for melt blending and granulation. The mixture was then vacuum dried at 50 °C for 3 h, followed by the addition of 4 kg of silanol condensation catalyst. The masterbatches were mixed to obtain a cross-linked polyethylene external insulation composition. The temperatures of each zone of the twin-screw extruder were set sequentially as follows: feed section: 145℃; compression zone 1: 155℃; compression zone 2: 165℃; mixing zone 1: 170℃; mixing zone 2: 175℃; venting section: 170℃; metering section: 165℃; die head: 165℃. The polyolefin resin matrix consisted of silane-modified polyethylene, metallocene linear low-density polyethylene, and ethylene-octene copolymer in a mass ratio of 72:12:16. The bifunctional interfacial bridging particles were added in the rear section of the extruder via side feeding. Inner extrusion layer: Two power transmission wires with a cross-sectional area of ​​2.5 mm² are prepared by stranding 196 tinned copper wires with a diameter of 0.127 mm. They adopt a concentric twisted structure with a twist pitch of 20 mm and a left-hand twisting direction. Four signal transmission wires with a cross-sectional area of ​​approximately 0.5 mm² are prepared by stranding 28 tinned copper wires with a diameter of 0.15 mm. The twist pitch is controlled at 12 mm, and the twisting direction is left-hand. Silicone rubber inner insulating compound is extruded and coated onto the surfaces of the power transmission wires and signal transmission wires. The temperature control in each zone of the extruder is as follows: Feeding section: 20~20℃. 5℃; Conveying section: 25~30℃; Die head: 45~55℃; Mold: 55~65℃; The thickness of the silicone rubber inner insulation layer outside the power transmission wire is 0.20mm, and the thickness of the silicone rubber inner insulation layer outside the signal transmission wire is 0.15mm; After extrusion, the wires continuously enter a 6m long hot air vulcanizing furnace for pre-vulcanization treatment. The temperature of the front section of the vulcanizing furnace is 170℃, and the temperature of the rear section is 185℃, so that the gel content of the silicone rubber inner insulation layer reaches 65%, and some bifunctional interface bridging particles are exposed on the surface of the silicone rubber inner insulation layer; Then, the temperature is cooled to 50℃ and immediately enters the outer insulation layer extrusion process; Outer layer extrusion: A cross-linked polyethylene outer insulation composition is extruded onto the outside of the pre-vulcanized silicone rubber inner insulation layer. The temperatures of each zone of the extruder are as follows: feeding section: 145℃; compression zone 1: 155℃; compression zone 2: 165℃; metering section: 175℃; die head: 180℃; die: 180℃. The thickness of the cross-linked polyethylene outer insulation layer of the power transmission wire is 0.30mm, and the thickness of the cross-linked polyethylene outer insulation layer of the signal transmission wire is 0.25mm. The amino groups exposed on the surface of the bifunctional interface bridging particles undergo a ring-opening reaction with the epoxy groups in the outer insulation layer to obtain power transmission wires and signal transmission wires coated with a composite insulation layer. Stranding and Composite Crosslinking: Power transmission wires and signal transmission wires coated with composite insulation are first placed in a hot water bath at 90℃ for 6 hours. After hot water treatment, each wire is placed at 23±2℃ and relative humidity of 50±10% for 24 hours to complete wet crosslinking. Four signal transmission wires coated with composite insulation are paired in pairs to form the first signal transmission pair and the second signal transmission pair. The two pairs are twisted in the right direction. The twist pitch of the first signal transmission pair is 23mm, and the twist pitch of the second signal transmission pair is 25mm. Two wires coated with composite insulation... The power transmission conductors and two sets of signal transmission pairs are fed into the cabling machine in a circumferentially spaced manner. The two power transmission conductors and the two sets of signal transmission pairs are positioned opposite each other, so that the power transmission conductors and signal transmission pairs are alternately distributed along the circumference of the bundled conductors. Left-hand cabling is used, with a cabling pitch of 40mm, forming a bundled conductor. A 25μm thick aluminum foil with a width of 20mm is spirally wrapped around the outside of the bundled conductors. The wrapping direction of the aluminum foil is opposite to the overall cabling direction, with a wrapping angle of 40° and an overlap rate of 30%. A 0.35mm² plated aluminum foil is placed along the axial direction of the bundle on the inside of the aluminum foil. Tin-copper drain lines ensure continuous contact between the drain lines and the aluminum foil metal surface. Next, tin-plated copper wires with a diameter of 0.12mm are braided around the aluminum foil wrapping layer. The braiding machine uses a 16-spindle structure, with 8 tin-plated copper wires per spindle. The braiding angle is controlled at 45°, the braiding pitch at 30mm, the braiding density at 90%, and the braiding tension at 10N, forming a composite shielding layer. Thermoplastic polyester elastomer (TPE-E) granules are dehumidified and dried at 100℃ for 4 hours. A single-screw extruder with a sheath is then used to extrude the sheath onto the surface of the composite shielding layer. The screw length-to-diameter ratio is 25:1, and the temperatures of each zone of the extruder are as follows: Feeding section: 180℃; Compression section 1: 195℃; Compression section 2: 205℃; Metering section: 215℃; Head: 220℃; Mold: 220℃, resulting in a sheath layer with a thickness of 0.70mm; The wire harness is cut to a design length of 1.5m, the sheath layer and composite shielding layer at the ends of the wire harness are removed, and crimped. The crimped ends of the wire harness are placed in the mold, and hot melt polyamide for low-pressure injection molding is used to perform integrated injection molding sealing on the ends and branches of the wire harness at 215℃ and 28bar, resulting in a composite shielded lightweight wire harness for gas circulation fans in new energy vehicles.

[0034] Example 2 The difference between Example 2 and Example 1 is that the mixing process is as follows: 100 kg of silicone rubber matrix is ​​added to a mixer and plasticized for 5 min at a rotor speed of 25 r / min and a cooling water temperature of 20°C. The temperature is 45°C. Then, 26 kg of fumed silica, 6.5 kg of bifunctional interface bridging particles from Example 1, 3.5 kg of hydroxyl silicone oil and 2 kg of vinyl silicone oil are added and mixed for 13 min at a speed of 35 r / min. Finally, 0.9 kg of peroxide crosslinking agent is added at 30°C to obtain silicone rubber internal insulating compound. Melt blending: 100 kg of polyolefin resin matrix, 6 kg of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 0.3 kg of hindered phenolic antioxidant, 0.2 kg of phosphite antioxidant, and 0.35 kg of copper ion inhibitor were first mixed at 300 r / min for 3 min, and then mixed at 600 r / min for 5 min to obtain a premix. The premix and 4 kg of bifunctional interface bridging particles from Preparation Example 1 were added to a co-rotating twin-screw extruder for melt blending and granulation. The mixture was then vacuum dried at 50°C for 3 h. Subsequently, 5 kg of silanol condensation catalyst masterbatch was added and mixed to obtain a cross-linked polyethylene external insulation composition. The remaining steps were consistent with those in Example 1.

[0035] Example 3 The difference between Example 3 and Example 1 is that the mixing process is as follows: 100 kg of silicone rubber matrix is ​​added to a mixer and plasticized for 5 min at a rotor speed of 25 r / min and a cooling water temperature of 20°C. The temperature is 45°C. Then, 32 kg of fumed silica, 9 kg of bifunctional interface bridging particles from Example 1, 5 kg of hydroxyl silicone oil, and 3 kg of vinyl silicone oil are added and mixed for 13 min at a speed of 35 r / min. Finally, 1.2 kg of peroxide crosslinking agent is added at 30°C to obtain silicone rubber internal insulating compound. Melt blending: 100 kg of polyolefin resin matrix, 8 kg of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 0.4 kg of hindered phenolic antioxidant, 0.3 kg of phosphite antioxidant, and 0.5 kg of copper ion inhibitor were first mixed at 300 r / min for 3 min, and then mixed at 600 r / min for 5 min to obtain a premix. The premix and 6 kg of bifunctional interface bridging particles from Preparation Example 1 were added to a co-rotating twin-screw extruder for melt blending and granulation. The mixture was then vacuum dried at 50°C for 3 h. Subsequently, 6 kg of silanol condensation catalyst masterbatch was added and mixed to obtain a cross-linked polyethylene external insulation composition. The remaining steps were consistent with those in Example 1.

[0036] Example 4 The difference between Example 4 and Example 2 is in the mixing process: 100 kg of silicone rubber matrix was added to a mixer and plasticized for 5 minutes at a rotor speed of 25 r / min and a cooling water temperature of 20°C, with a temperature of 45°C. Then, 26 kg of fumed silica, 6.5 kg of bifunctional interface bridging particles from Preparation Example 1, 3.5 kg of hydroxyl silicone oil, 2 kg of vinyl silicone oil, and 2.5 kg of phenyl silicone oil were added and mixed for 13 minutes at a speed of 35 r / min. Then, 0.9 kg of peroxide crosslinking agent was added at 30°C to obtain the silicone rubber internal insulating compound. The remaining steps were the same as in Example 2.

[0037] Example 5 The difference between Example 5 and Example 4 is in the mixing process: 100 kg of silicone rubber matrix was added to a mixer and plasticized for 5 minutes at a rotor speed of 25 r / min and a cooling water temperature of 20°C, with a temperature of 45°C. Then, 26 kg of fumed silica, 6.5 kg of bifunctional interface bridging particles from Preparation Example 1, 1 kg of nano-cerium oxide, 3.5 kg of hydroxyl silicone oil, 2 kg of vinyl silicone oil, and 2.5 kg of phenyl silicone oil were added and mixed for 13 minutes at a speed of 35 r / min. Then, 0.9 kg of peroxide crosslinking agent was added at 30°C to obtain the silicone rubber internal insulating compound. The remaining steps were the same as in Example 4.

[0038] Example 6 The difference between Example 6 and Example 5 is that the silicone rubber matrix is ​​methyl vinyl silicone rubber; the remaining steps are the same as in Example 5.

[0039] Example 7 The difference between Example 7 and Example 5 is that the silicone rubber matrix is ​​methyl vinyl phenyl silicone rubber; the remaining steps are the same as in Example 5.

[0040] Example 8 The difference between Example 8 and Example 5 is that the polyolefin resin matrix is ​​silane-modified polyethylene; the remaining steps are the same as in Example 5.

[0041] Example 9 The difference between Example 9 and Example 5 is that the polyolefin resin matrix is ​​metallocene linear low-density polyethylene; the remaining steps are the same as in Example 5.

[0042] Example 10 The difference between Example 10 and Example 5 is that the polyolefin resin matrix is ​​an ethylene-octene copolymer; the remaining steps are the same as in Example 5. Comparative Example

[0043] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that a single-layer cross-linked polyethylene insulation layer is used instead of the composite insulation layer composed of a silicone rubber inner insulation layer and a cross-linked polyethylene outer insulation layer; a single-layer aluminum foil shielding layer is used instead of the composite shielding layer composed of an aluminum foil wrapping layer and a tinned copper wire braided mesh; a polyvinyl chloride sheath layer is used instead of a thermoplastic polyester elastomer sheath layer; and a heat shrink tubing branch protection and a waterproof connector are used instead of an integrated injection-molded sealing structure; the remaining steps are the same as in Example 1.

[0044] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the bifunctional interface bridging particles in the silicone rubber inner insulating layer and the cross-linked polyethylene outer insulating layer are replaced in equal amounts with the interface particles grafted with vinyl silane only obtained in Preparation Example 2; the remaining steps are the same as in Example 1.

[0045] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the bifunctional interface bridging particles in the silicone rubber inner insulating layer and the cross-linked polyethylene outer insulating layer are replaced in equal amounts with the interface particles grafted with vinyl silane only obtained in Preparation Example 3; the remaining steps are the same as in Example 1.

[0046] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that, in the mixing process: 100 kg of silicone rubber matrix was added to a mixer and plasticized for 5 min at a rotor speed of 25 r / min and a cooling water temperature of 20°C, at a temperature of 45°C. Then, 20 kg of fumed silica and 4 kg of bifunctional interface bridging particles from Example 1 were added and mixed for 13 min at a speed of 35 r / min. Finally, 0.6 kg of peroxide crosslinking agent was added at 30°C to obtain the silicone rubber internal insulating compound. The remaining steps were the same as in Example 1. Performance testing experiment

[0047] Temperature resistance performance: Tested according to ISO 19642-2:2023, Test Methods for Thermal Aging and Mechanical Properties of Automotive Cables. Five 300mm long samples were cut from both the power transmission wire and signal transmission wire of each sample. The samples were aged in a forced-ventilation thermal aging chamber at 125±2℃ for 1000 hours, and then placed at 23±2℃ and 50±10% relative humidity for 16 hours. The elongation at break of the insulation layer before and after aging was measured at a tensile speed of 250mm / min. The elongation at break retention rate was calculated as "Elongation at break retention rate = Elongation at break after aging / Elongation at break before aging × 100%", and the lower of the results obtained for the power transmission wire and signal transmission wire was used as the sample result. A sample was deemed to have reached the 125℃ temperature resistance rating if the elongation at break retention rate was not less than 80%.

[0048] Shielding performance: The test is carried out with reference to the triaxial tube-in-tube method specified in IEC 62153-4-7:2021+A1:2025. A complete wire harness assembly with a length of 1.0 m is taken, the connectors are properly mated, and the aluminum foil wrapping layer and tinned copper wire braided mesh form a 360° continuous termination with the shielding end of the connector; a 50Ω vector network analyzer is used to scan in the frequency range of 100 kHz to 1 GHz, and the shielding attenuation at 100 MHz and 1 GHz is recorded respectively. Three pieces of each group of samples are tested, and the average value is taken as the test result. A larger shielding attenuation value indicates better shielding performance.

[0049] Waterproof performance: The test is carried out with reference to the test method for IPX7 protection level in ISO 20653:2023 with extended water immersion conditions. The connectors are properly mated and unused holes are blocked, so that the lowest point of the sample is 1.0 m below the water surface and immersed in water continuously for 24 h; after taking out the sample, the surface is wiped dry and placed at room temperature for 30 min, it is checked whether water enters the connectors and branches, then a 500 V DC voltage is applied between each conductor and the composite shielding layer for 1 min to measure the insulation resistance, and the minimum value among all measured values is taken as the test result. When the insulation resistance is not less than 100 MΩ and there is no visible water ingress inside, the waterproof sealing performance is judged to be qualified.

[0050] Wire harness weight: Each sample is made into a wire harness assembly with a length of 1.5 m and complete and consistent connectors and branch structures, placed for 24 h under the conditions of 23±2°C and relative humidity of 50±10%, and then weighed with an electronic balance with a division value of 0.1 g. Five pieces of each group of samples are tested, and the arithmetic mean value is taken as the wire harness weight.

[0051] Vibration durability: The test is carried out with reference to the test principles for mechanical loads of electrical and electronic equipment for road vehicles specified in ISO 16750-3:2023. According to the actual installation state of the wire harness on the gas circulation fan, the connectors, branch positions and fixing points are installed on the vibration test bench, logarithmic frequency sweeping is carried out in the range of 10 to 2000 Hz, the peak acceleration is 20g, vibration is performed for 8 h in each of three mutually perpendicular directions, and the total vibration time is 24 h. The conduction state is monitored during the test, and the contact resistance of each terminal is measured by the four-wire method before and after the test, and the maximum value of the contact resistance variation is taken as the test result; at the same time, it is checked whether the connectors are loose, the sheath is cracked, and the composite insulating layer has interface delamination. When the contact resistance variation is less than 1.0 mΩ and there is no looseness, cracking or obvious delamination, the vibration durability performance is judged to be qualified.

[0052] Salt spray test: The test is carried out with reference to the neutral salt spray test method specified in ISO 9227:2022. Place the complete wire harness assembly in a salt spray test chamber, use a sodium chloride solution with a mass fraction of 5.0±0.5%, set the test temperature at 35±2℃, keep the pH of the salt spray sedimentation solution at 6.5 to 7.2, and conduct the test continuously for 96 hours. After the test, gently rinse the sample surface with deionized water, leave it at room temperature for 2 hours, inspect the corrosion of the terminals, shielding layer, connectors and branches, measure the contact resistance of the terminals before and after the test, and take the maximum variation of the contact resistance as the test result. When the variation of contact resistance is less than 1.0mΩ, no red rust exists and the wire harness functions normally, the salt spray performance is judged to be qualified.

[0053] Table 1 Performance test data of the lightweight wire harness

[0054] In combination with Example 1 and Comparative Example 1, Comparative Example 1 adopts single-layer cross-linked polyethylene insulation, single-layer aluminum foil shielding, polyvinyl chloride sheath and heat-shrinkable tube branch protection, whose shielding effectiveness at 100MHz and 1GHz is only 38.2dB and 28.6dB respectively, and the insulation resistance after water immersion is only 48MΩ. In contrast, the lightweight wire harness of Example 1 has excellent electromagnetic shielding, waterproof sealing, vibration resistance and lightweight performance, which indicates that the composite shielding layer, thin-wall TPE-E sheath layer and integrated injection-molded sealing structure can give consideration to electromagnetic shielding, waterproof sealing, vibration resistance and lightweight performance.

[0055] In combination with Example 1 and Comparative Examples 2 to 4, the bridging particles used in Comparative Example 2 only contain vinyl groups and cannot form an effective connection with the epoxy groups in the outer cross-linked polyethylene insulation layer; the bridging particles used in Comparative Example 3 only contain amino groups and cannot fully participate in the co-crosslinking of the inner silicone rubber insulation layer, so both of them show different degrees of interface delamination after the vibration test. In Comparative Example 4, hydroxy silicone oil and vinyl silicone oil are not added, the dispersibility of the filler and the uniformity of the silicone rubber crosslinking network are reduced, and its temperature resistance performance and vibration durability performance are further decreased. The above results show that the vinyl groups and amino groups on the surface of the dual-functional interface bridging particles react with the inner and outer insulation layers respectively, which is the key to improving the interface stability of the composite insulation layer.

[0056] In combination with Examples 1 to 3, Example 2 has higher temperature resistance performance and waterproof sealing performance than Example 1, which indicates that appropriately increasing the dosage of fumed silica, dual-functional interface bridging particles, reactive compatibilizing components and crosslinking system is beneficial to improving the crosslinking integrity of the insulation layer and the interface bonding stability; after Example 3 further increases the dosage of each component, the performance is not further improved, which shows that excessively high dosages of inorganic filler and crosslinking components increase the viscosity and local rigidity of the system, and are not conducive to the uniform dispersion of particles and the release of interface stress.

[0057] Combining Examples 2, 4, and 5, Example 4, based on Example 2, added phenyl silicone oil, which improved the temperature resistance from 87.9% to 90.8%, and reduced the change in contact resistance after vibration testing from 0.39 mΩ to 0.34 mΩ. This indicates that phenyl silicone oil can cooperate with methyl vinyl phenyl silicone rubber to improve the low-temperature mobility of silicone rubber molecular chains and the dispersion state of fillers. Example 5, further adding nano-cerium oxide, improved the temperature resistance to 94.2%, indicating that nano-cerium oxide can cooperate with the composite antioxidant system to slow down the thermo-oxidative aging of the inner insulating layer of silicone rubber.

[0058] In conjunction with Examples 5-7, Examples 6 and 7 used only methyl vinyl silicone rubber or methyl vinyl phenyl silicone rubber as the silicone rubber matrix, respectively, and their overall performance was lower than that of Example 5, indicating that the combined use of the two silicone rubbers can further improve the performance of lightweight wire harnesses.

[0059] Combining Examples 5 and 8-10, Examples 8-10 each used only one type of polyolefin as the resin matrix for the outer insulation layer. Examples 9 and 10 showed a heat aging retention rate of less than 80% and interfacial delamination after vibration. This indicates that the combination of silane-modified polyethylene, metallocene linear low-density polyethylene and ethylene-octene copolymer has a synergistic effect on constructing a heat-resistant crosslinking network, improving processing and molding, and buffering interfacial stress.

[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle, characterized in that: The assembly includes bundled wires, a composite shielding layer covering the outside of the bundled wires, a sheathing layer covering the outside of the composite shielding layer, and an integrated injection-molded sealed connector disposed at the ends and branches of the wire harness; the bundled wires include at least one power transmission wire covered with a composite insulation layer. The system includes at least one signal transmission wire coated with a composite insulation layer; the composite insulation layer comprises an inner silicone rubber insulation layer covering the outside of the wire and an outer cross-linked polyethylene insulation layer covering the outside of the inner silicone rubber insulation layer; the raw materials of the inner silicone rubber insulation layer include the following components in parts by weight: 100 parts silicone rubber matrix, 20-32 parts fumed silica, 4-9 parts bifunctional interface bridging particles, 2-5 parts hydroxyl silicone oil, 1-3 parts vinyl silicone oil, and 0.6-1.2 parts peroxide crosslinking agent; the raw materials of the outer cross-linked polyethylene insulation layer include the following components in parts by weight: 100 parts polyolefin resin matrix, 4-8 parts ethylene-methyl acrylate-glycidyl methacrylate copolymer, 2-6 parts bifunctional interface bridging particles, and 4-6 parts silanol condensation catalyst masterbatch; the bifunctional interface bridging particles include an inorganic core, a silica shell coating the surface of the inorganic core, and vinyl silane and amino silane grafted onto the surface of the silica shell.

2. The composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 1, characterized in that: The silicone rubber matrix comprises methyl vinyl silicone rubber and methyl vinyl phenyl silicone rubber in a mass ratio of (75-90):(10-25).

3. The composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 2, characterized in that: The raw materials for the inner insulating layer of the silicone rubber also include 1 to 4 parts by weight of phenyl silicone oil.

4. The composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 1, characterized in that: The polyolefin resin matrix includes silane-modified polyethylene, metallocene linear low-density polyethylene and ethylene-octene copolymer, and the mass ratio is (65-78):(8-15):(10-18).

5. The composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 1, characterized in that: The preparation method of the bifunctional interface bridging particles includes the following steps: 100 parts by weight of nano-alumina were dispersed in 250-350 parts by weight of anhydrous ethanol, 20-30 parts by weight of deionized water and 2-3 parts by weight of ammonia were added, 30-40 parts by weight of tetraethyl orthosilicate were added dropwise, and the reaction was carried out at 40-60℃ for 2-4 hours. After filtration, washing and drying, core-shell particles coated with a silica shell were obtained. 100 parts by weight of core-shell particles were dispersed in a mixture of 100-180 parts by weight of ethanol and 5-12 parts by weight of deionized water. 2.0-4.0 parts by weight of vinyltriethoxysilane and 0.5-1.5 parts by weight of γ-aminopropyltriethoxysilane were added, and the pH of the system was adjusted to 4.5-5.

5. The mixture was reacted at 55-70°C for 2-4 hours. After filtration, washing, and vacuum drying at 90-110°C, bifunctional interfacial bridging particles were obtained.

6. The composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 1, characterized in that: The raw material of the inner insulating layer of the silicone rubber also includes 0.5 to 1.5 parts by weight of nano-cerium oxide.

7. The composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 1, characterized in that: The raw materials for the cross-linked polyethylene outer insulation layer also include the following components in parts by weight: 0.2 to 0.4 parts of hindered phenolic antioxidant, 0.1 to 0.3 parts of phosphite antioxidant, and 0.2 to 0.5 parts of copper ion inhibitor.

8. A method for manufacturing a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle as described in any one of claims 1-7, characterized in that: Includes the following steps: Mixing: The silicone rubber matrix, fumed silica, bifunctional interface bridging particles, hydroxyl silicone oil and vinyl silicone oil are mixed, and a peroxide crosslinking agent is added at a mixing temperature not higher than 60°C to obtain silicone rubber internal insulating compound. Melt blending: Polyolefin resin matrix, ethylene-methyl acrylate-glycidyl methacrylate copolymer, and bifunctional interfacial bridging particles are melt blended and granulated, and then mixed with silanol condensation catalyst masterbatch to obtain cross-linked polyethylene external insulation composition; Inner layer extrusion: The silicone rubber inner insulation compound is extruded and coated onto the surface of the power transmission wire and signal transmission wire, and the extruded silicone rubber inner insulation layer is pre-vulcanized. Extrusion of outer layer: Cross-linked polyethylene outer insulation composition is extruded on the outside of the pre-vulcanized silicone rubber inner insulation layer to obtain power transmission wires and signal transmission wires covered with composite insulation layer; Stranded composite: Power transmission wires and signal transmission wires covered with composite insulation layers are first wet-crosslinked and then stranded to form bundled wires. A composite shielding layer and a sheath layer are applied sequentially to the outside of the bundled wires, and the ends and branches of the wire harness are integrally injection-molded and sealed to obtain a composite shielded lightweight wire harness for gas circulation fans of new energy vehicles.

9. A method for manufacturing a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 8, characterized in that: In the stranding and composite step, the composite shielding layer includes an aluminum foil wrapping layer and a tin-plated copper wire braided mesh.

10. The manufacturing method of a composite shielded lightweight wiring harness for a gas circulation fan in a new energy vehicle according to claim 9, characterized in that: In the stranding and bonding step, the raw material of the sheath layer includes thermoplastic polyester elastomer with a thickness of 0.5-1.0 mm.